GIT2 Acts as a Systems-Level Coordinator of Neurometabolic Activity and Pathophysiological Aging - Martin, Bronwen; Chadwick, Wayne; Janssens, Jonathan; Premont, Richard T.; Schmalzigaug, Robert; Becker, Kevin G.; Lehrmann, Elin; Wood, William H.; Zhang, Yongqing; Siddiqui, Sana; Park, Sung-Soo; Cong, Wei-na; et al. (Frontiers in Endocrinology, 2016)
Aging represents one of the most complicated and highly integrated somatic processes. Healthy aging is suggested to rely upon the coherent regulation of hormonal and neuronal communication between the central nervous system and peripheral tissues. The hypothalamus is one of the main structures in the body responsible for sustaining an efficient interaction between energy balance and neurological activity and therefore likely coordinates multiple systems in the aging process. We previously identified, in hypothalamic and peripheral tissues, the G protein-coupled receptor kinase interacting protein 2 (GIT2) as a stress response and aging regulator. As metabolic status profoundly affects aging trajectories we investigated the role of GIT2 in regulating metabolic activity. We found that genomic deletion of GIT2 alters hypothalamic transcriptomic signatures related to diabetes and metabolic pathways. Deletion of GIT2 reduced whole animal respiratory exchange ratios away from those related to primary glucose usage for energy homeostasis. GIT2 knockout (GIT2KO) mice demonstrated lower insulin secretion levels, disruption of pancreatic islet beta cell mass, elevated plasma glucose and insulin resistance. High-dimensionality transcriptomic signatures from islets isolated from GIT2KO mice indicated a disruption of beta cell development. Additionally, GIT2 expression was prematurely elevated in pancreatic and hypothalamic tissues from diabetic-state mice (db/db), compared to age-matched wild type controls, further supporting the role of GIT2 in metabolic regulation and aging. We also found that the physical interaction of pancreatic GIT2 with the insulin receptor and insulin receptor substrate 2 was diminished in db/db mice compared to wild type mice. Therefore GIT2 appears to exert a multidimensional ‘keystone’ role in regulating the aging process by coordinating somatic responses to energy deficits.